Qualitative release assessment for the re-introduction of HPAI H5N1 virus from neighboring countries into Ghana - Turkson, P. K. (International Food Policy Research Institute, 2008)
By December 2007, there was a continuum of Highly Pathogenic Avian Influenza (HPAI) H5N1 affected countries along the West African coast from Côte d’Ivoire to Cameroon. Eight West African countries (Nigeria, Niger, Cameroon, Burkina Faso, Côte d’Ivoire, Ghana, Togo and Benin) have all reported outbreaks. Benin, Nigeria and Togo reported new outbreaks on May 1, 2008, July 25, 2008, and November 13, 2008, respectively (OIE 2008). The risk of virus circulation and re-infection/re-introduction is high in the sub-region. There is constant movement of people and goods and thus trade between them. Recently, a new virus strain was isolated in Nigeria, raising more concerns in the sub-region (OIE 2008). In November 2008, a risk assessment stakeholder workshop was held in Accra for Ghanaian participants. Participants identified re-introduction of the virus into Ghana as a major risk. The Veterinary Services Directorate (VSD 2007) gives an overview of the risk for HPAI introduction into Ghana: “Ghana borders Togo to the east, Burkina Faso to the north and Côte d’Ivoire to the west. All these four countries have recorded outbreaks of the HPAI H5N1 virus in their respective countries, starting in April 2006 in Burkina Faso and Côte d’Ivoire and in April 2007 and June 2007 in Ghana and Togo, respectively. There are approved entry points between the countries and there exists a very high level of movement of both goods, including live animals and animal products, and people of the four countries. There are also unapproved routes, involving the illegal movement of animals and animal products across the sub-region. These unapproved routes can act as channels for the introduction of trans-boundary animal diseases into any of the four countries. Uncontrolled movement of live poultry and poultry products across the borders poses a serious threat to the animal health, especially [via] avian influenza, of any of the countries in the sub-region. Due to the artificial boundaries and the mix of socio-cultural ties of citizens of these countries, it is always very difficult to enforce quarantine measures in the event of outbreaks of trans-boundary animal diseases in any of the above countries.”